Sym-to-real Emulation and Low-cost Prototyping for Undergraduate Introductory Robotics - Revoredo, Téo Cerqueira; Guidine, Felipe Kremser; Vieira, Renan Porto (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Computer emulation and experimentation are natural parts of research and development in engineering and prototyping their natural extension when it comes to test and validation of proposed solutions in different scenarios. A prototype tends to be a low cost solution which helps to obtain initial feedback and to adjust algorithms, circuits etc before starting product development, reducing time in accomplishing the final solution. In an engineering faculty, a prototype can be more than that, presenting itself as a tool to provide students with the opportunity to engage in development of engineering tools, design mechanical parts, electronic circuits, integrate sensors and actuators and test solutions which go beyond the repetition of traditional practices in laboratories, result of knowledge already solidified over the years. Educational robotics, as well as small scale prototyping of different engineering systems, are inserted as agents of changes in this model of repetitions, as they demand the participation of a group of students in the conception and modeling of a problem and its solution helping them to develop some concepts that are sometimes rarely addressed in conventional disciplines, such as teamwork, self-development and creativity. In such scenario, this paper briefly presents some recent works developed at the Department of Electronic and Telecommunication Engineering (DETEL) of the State University of Rio de Janeiro (UERJ) based on sym-to-real emulation and low cost 3D-printing prototyping with special focus on a simple arduino-based cal-like robot with non holonomic constraints with is used as experimental apparatus for undergraduate disciplines, end-of-course works, research (scientific initiation and master), teaching and also competitions.